Some Endpoint Results for β-Generalized Weak Contractive Multifunctions - H. Alikhani; D. Gopal; M. A. Miandaragh; Sh. Rezapour; N. Shahzad (The Scientific World Journal)
We introduce β-generalized weak contractive multifunctions and give some results about endpoints of the multifunctions. Also, we give some results about role of a point in the existence of endpoints.